Penerapan Teknik Pengambilan Gambar oleh Director of Photography pada Produksi Video Feature "Melodi Bambu" - Guntur Aghni Triguna; Encang Saepudin; Ari Agung Prastowo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This Final Project report discusses the visual design process by the author as Director of Photography (DoP) in the creation of a feature video entitled "Bamboo Melody: Reviving a Traditional Symphony." This work aims to highlight the challenges faced in preserving the art of angklung music in the modern era, particularly the low interest of Generation Z in traditional culture. Angklung, which is one of Indonesia's cultural heritages, is experiencing a regeneration crisis, where the successors of this tradition are decreasing. In this context, it is important to convey the meaning and cultural values of angklung to the younger generation in a relevant and engaging way. The method of writing this report uses a descriptive approach that includes three production stages: pre-production, production, and post-production. Each stage is designed systematically and reflectively to ensure that the intended message is well received by the audience. In the pre-production stage, the author designed a visual concept that aligns with the theme and purpose of the work, namely to depict the meaningful philosophy of the angklung sound. In the production stage, shooting techniques were carefully selected to ensure aesthetics and clear communication in each frame. The results of the application of appropriate shooting techniques are proven to be able to present the philosophical value of angklung aesthetically and communicatively. Through powerful visuals, viewers can experience the depth of meaning behind this traditional musical instrument. Furthermore, this work concludes with testimonials from young angklung players and an angklung performance at Saung Angklung Udjo, illustrating concrete efforts to preserve angklung culture. This section emphasizes the importance of youth involvement in cultural regeneration, demonstrating that with a creative approach, the angklung's sound philosophy can be revived and well-received by Generation Z. Therefore, this work not only conveys solutions in the form of discourse but also provides a concrete illustration of cultural preservation through contemporary media that is accessible and understandable to the younger generation.